2018
DOI: 10.1136/bcr-2018-225079
|View full text |Cite
|
Sign up to set email alerts
|

Gardener-associated fibroma: an unusual cause of upper airway obstruction

Abstract: We present the first case of upper airway obstruction secondary to a retropharyngeal Gardner-associated fibroma (GAF). A 16-month-old infant presented with a 3-month history of worsening dyspnoea and apnoeic episodes. Examination revealed stridor and left-sided retropharyngeal asymmetry. MRI demonstrated a mass in the retropharynx. Tracheostomy and pharyngeal biopsy under anaesthesia were performed, and histology confirmed a diagnosis of GAF. The mass was excised using a transcervical approach, and postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
3
0
1
Order By: Relevance
“…3 Our patient is the first reported GAF presenting in the floor of mouth. Pinto et al 7 reported a retropharyngeal GAF presenting with upper airway obstruction in a 16-month-old.…”
Section: Discussionmentioning
confidence: 99%
“…3 Our patient is the first reported GAF presenting in the floor of mouth. Pinto et al 7 reported a retropharyngeal GAF presenting with upper airway obstruction in a 16-month-old.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Other changes that are potentially associated with Gardner syndrome include loss of DNA methylation, an aberration of the RAS gene (located on chromosome 12), aberration of TP53 gene (chromosome 17) and deletion of the colon cancer gene (chromosome 18). [9][10][11]…”
Section: Pathogenesismentioning
confidence: 99%
“…Ein genetischer Zusammenhang mit der Entwicklung des Gardner-Syndroms wurde in einer Mutation des Gens für adenomatöse Polyposis coli (APC) gezeigt, das auf Chromosom 5 liegt. Dieses Tumorsuppressorgen ist für die Produktion des APC-Proteins verantwortlich, welches das Zellwachstum im Zellzyklus reguliert [167][168][169].…”
Section: Meningeomeunclassified
“…A genetic correlation with the development of Gardner's syndrome was identified in a mutation of the gene for adenomatous polyposis coli (APC) located on chromosome 5. This tumor suppressor gene is responsible for the production of the APC protein regulating the cell growth in the cell cycle [167][168][169].…”
Section: Bone Tumors 24121 Osteomas and Gardner's Syndromementioning
confidence: 99%